2022
DOI: 10.1186/s12903-022-02392-y
|View full text |Cite
|
Sign up to set email alerts
|

Translation and validation of Sinhala version of modified EORTC QLQ-OH15 in oral cancer patients who receive radiotherapy with or without chemotherapy in Sri Lanka

Abstract: Background The recognition of patient-reported outcomes for oral cancer is important in improving patients’ quality of life. The aim of this study was to translate and validate the modified Sinhala version of the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Oral Health Module (EORTC QLQ-OH15). Methods A cross-sectional study was conducted to validate the EORTC QLQ-OH15 that was modified after adding two … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…This was the first prospective study carried out among the oral cancer patients who receive RT alone or with chemotherapy to assess their OHRQOL and the changes of OHRQOL within three months post RT in Sri Lanka. The OHRQOL was assessed by using modified EORTC QLQ-OH15 questionnaire which was validated for the oral cancer patients who received RT alone or with chemotherapy in Sri Lanka [ 23 ]. The OHRQOL in oral cancer patients became extremely poor during the last week of RT compared to baseline due to RT alone or with chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was the first prospective study carried out among the oral cancer patients who receive RT alone or with chemotherapy to assess their OHRQOL and the changes of OHRQOL within three months post RT in Sri Lanka. The OHRQOL was assessed by using modified EORTC QLQ-OH15 questionnaire which was validated for the oral cancer patients who received RT alone or with chemotherapy in Sri Lanka [ 23 ]. The OHRQOL in oral cancer patients became extremely poor during the last week of RT compared to baseline due to RT alone or with chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are two variables to assess the patients’ satisfaction on information they gained during treatment and two variables to assess OHRQOL among denture wearers. A high score represents a high level of symptoms and low level of OHRQOL [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Surgery, radiotherapy and chemotherapy are the main modalities of treatment however, as noted above, there is a bias to primary surgery 56 . Oral cancer patients with advanced stages of the disease or who have close surgical margins are recommended for postoperative external beam radiotherapy 59 . Best practice is to initiate radiotherapy within 6 weeks of surgery, but this is frequently significantly stretched due to the demand on radiotherapy and limitation of radiotherapy facilities and patient related factors such as delayed wound healing 60 …”
Section: Differences Between Districts In the Distribution Of Oral Ca...mentioning
confidence: 99%
“…Dysphagia, psychiatric disorders and trismus seriously decrease QoL [ 4 , 5 ]. However, speech is one of the most distressing problems for patients [ 6 – 8 ]. In previous studies, researchers confirmed that chemoradiotherapy and surgery affected patients’ speech intelligibility [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%